Peran Green Human Resource Management dalam Implementasi CSR Pengelolaan Lingkungan yang Berkelanjutan di Masa Pandemi COVID-19 - Gugus Wijonarko; Amaliyah Amaliyah (IPB University, 2023)
Environmental impacts continue to occur as a result of various human activities. In the midst of the COVID-19 pandemic, many companies are experiencing financial problems that affect the implementation of CSR, especially in the environmental field. As we know, all elements of the government, society, companies are focused on handling the pandemic, but environmental problems continue to occur. This study aims to describe the relationship between GHRM and the implementation of sustainable CSR in the environmental field by PT. Pelindo III in managing the environment amid the COVID-19 pandemic. The method used in this research is qualitative description. The data collection process was carried out through three stages, namely conducting a literature study, collecting secondary data and conducting in-depth interviews with employees in charge of implementing CSR. The results showed that at PT. Pelindo III, the GHRM concept applied has a role in the transformation of employee behavior into environmentally friendly employees. Ideas or initiatives on environmental prevention and management are implemented in CSR activities such as tree planting, mangroves, community empowerment in the form of tourist villages, hydroponic villages and other activities. On the other hand, environmental impact prevention activities are also carried out by implementing the green port concept at ports as well as a paperless policy, reducing the use of plastic and segregating waste. To maintain a green culture, employees who consistently contribute to environmental issues are given rewards.